Aplicación móvil de gestión de actividades en la Bancada Unión por la Esperanza-UNES - Mendoza Andrade, Guido Adrián (2023)
The main objective of this titling project was the development of an information system and management of activities for the Bancada Unión por la Esperanza (UNES). For the development of the system, the SCRUM methodology was used, which consists of 4 essential phases for the execution of a project, which are: planning and estimation, execution and development, review and retrospectives, launch; the first phase allowed defining the tasks to be developed in order of priority and establishing the functionalities of the system through the analysis of user stories, this provided a clear guide to advance in the project efficiently, in the second and third phases carry out the development and documentation of each module in order of priority specified in the product backlog and in turn evaluate the results obtained during development, in the last phase of the launch the modules that met the acceptance criteria were delivered to the relevant stakeholders. For the technology transfer process, the complete system was delivered, including the source code and documentation (User Manual). At the end of the objectives, a highly accessible system was obtained as a result that facilitates the publication and obtaining of information both from the Bench and its assembly members, allowing to significantly improve communication and information security. These benefits contribute to strengthening the work of the bench and maximizing the impact of its activities for the benefit of society.